A meta-analysis comparing ALIF, PLIF, TLIF and LLIF - Teng, Ian; Han, Julian; Phan, Kevin; Mobbs, Ralph (Journal of clinical neuroscience, 2017)
•ALIF, PLIF, TLIF and LLIF had similar fusion rates.•ALIF achieved better postoperative disc height and postoperative segmental lordosis.•TLIF had better Oswestry Disability Index (ODI) scores.•PLIF had the greatest blood loss.•Complication rates were similar across approaches. Lumbar interbody fusions have been widely used to treat degenerative lumbar disease that fails to respond to conservative treatment. This procedure is divided according to its approach: anterior lumbar interbody fusion (ALIF), posterior lumbar interbody fusion (PLIF), transforaminal lumbar interbody fusion (TLIF) and lateral lumbar interbody fusion (LLIF). Each approach has its own theoretical advantages and disadvantages; however, there have been no studies that compared these. Various full-text databases were systematically searched through December 2015. Data regarding the radiological, operative and clinical outcomes of each lumbar interbody fusion were extracted. All outcomes were pooled using random effects meta-analysis, with the relative risk (RR) and/or weighted mean difference (WMD) as the summary statistic. Thirty studies met the inclusion criteria. The ALIF procedure has been studied most intensively, followed by PLIF, TLIF and LLIF respectively. All four approaches had similar fusion rates (p=0.320 & 0.703). ALIF has superior radiological outcome, achieving better postoperative disc height (p=0.002 & 0.005) and postoperative segmental lordosis (p=0.013 & 0.000). TLIF had better Oswestry Disability Index scores (p=0.025 & 0.000) while PLIF had the greatest blood loss (p=0.032 & 0.006). Complication rates were similar between approaches. Other comparisons were either inconclusive or lacked data. There was marked less studies comparing against LLIF. Each approach has their own risks and benefits but similar fusion rates. Despite the large number of studies, there is little data overall when comparing specific aspects of lumbar interbody fusions. More studies, especially RCTs are needed to further explore this topic.